2023
DOI: 10.1038/s41598-023-38137-2
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing saltiness perception by chemosensory interaction: an fMRI study

Abstract: Neuroimaging studies that focus on taste, odor, and their interactions can specify their capability to elicit brain regions responsible for flavor perception and reward. Such information would be useful for formulating healthy food products, such as low salt food. In this study, a sensory experiment was conducted to investigate the capability of cheddar cheese odor, monosodium glutamate (MSG), and their interactions to enhance saltiness perception and preference of NaCl solutions. The activated brain areas in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…Odor compounds with salty flavor characteristics, aligned with the taste of salt, notably enhance the perception of saltiness in the human body. This phenomenon, termed odor-induced salty taste enhancement (OISE), represents an effective strategy for enhancing the perception of salty taste in low-salt foods [ 5 , 41 , 63 , 64 , 65 ]. Multiple studies have reported the potential of aroma substances to enhance the flavor of low-salt foods [ 53 , 66 ].…”
Section: Detailed Multisensory Synergistic Effectmentioning
confidence: 99%
See 2 more Smart Citations
“…Odor compounds with salty flavor characteristics, aligned with the taste of salt, notably enhance the perception of saltiness in the human body. This phenomenon, termed odor-induced salty taste enhancement (OISE), represents an effective strategy for enhancing the perception of salty taste in low-salt foods [ 5 , 41 , 63 , 64 , 65 ]. Multiple studies have reported the potential of aroma substances to enhance the flavor of low-salt foods [ 53 , 66 ].…”
Section: Detailed Multisensory Synergistic Effectmentioning
confidence: 99%
“…In the cross-modal odor-flavor-flavor ternary system, such as odor-sour-salty mixtures, sour taste not only directly enhances salty taste, but also amplifies salty taste perception by boosting salt-related odor perception [ 5 ]. Similarly, the combination of MSG and cheese odor with NaCl has been found to enhance salty taste perception more than when each component is used alone [ 63 , 64 , 96 ]. Furthermore, the integration of trigeminal nerve sensation, triggered by stimuli like capsaicin, with taste and aroma sensation in the OFC of the brain heightens sensitivity to taste and odor, thereby enhancing salty taste perception in complex food substrates [ 87 , 93 ].…”
Section: Detailed Multisensory Synergistic Effectmentioning
confidence: 99%
See 1 more Smart Citation